Two new species of Tomocerus (Ocreatomurus) Yu from Xizang, China (Collembola, Tomoceridae) - Yu, Daoyuan; Xue, Huiying; Zhang, Feng (Zootaxa, 2025)
Two new species of Tomocerus (Ocreatomurus) are described from Gyirong Valley, Xizang Autonomous Region, China. Tomocerus (Ocreatomurus) gyirongensis sp. nov. and Tomocerus (Ocreatomurus) oppositus sp. nov. are both similar to Tomocerus (Ocreatomurus) spinulus Chen & Christiansen, 1998 in the absence of blunt dorsal chaetae on manubrium and presence of single large distal dental spines, but these three species can be distinguished mainly by body color, number of tibiotarsal strong inner chaetae, number and position of manubrial prominent chaetae, and arrangement of basal dental spines.